Foamed nickel loaded phosphorus modified cobalt-copper bimetallic catalytic electrode, preparation method thereof and application of foamed nickel loaded phosphorus modified cobalt-copper bimetallic catalytic electrode in electro-catalysis nitrate reduction

By depositing electrocatalytic electrodes of phosphorus modified cobalt-copper bimetallic catalyst on the foam nickel support, the two-step series process of nitrate reduction reaction was optimized, and the problem of NO2-intermediate accumulation was solved, significantly improving the yield of ammonia and Faraday efficiency.

CN119710797APending Publication Date: 2025-03-28CHINA CONSTR EIGHT ENG DIV CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411674987.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when the ammonia is electrochemically synthesized under normal temperature conditions, the yield and Faraday efficiency of ammonia are lower than the target value, and the accumulation of NO2-intermediates in the nitrate reduction reaction leads to a decrease in selectivity of ammonia.

Method used

A cobalt-copper bimetallic catalytic electrode was used to modify the cobalt-copper bimetallic catalyst by electrodeposition method on the nickel foam support, and the two-step series reaction was optimized to avoid excessive accumulation of NO2-.

Benefits of technology

When the applied voltage is -0.4V vs RHE, the Faraday efficiency exceeds 95%, the ammonia yield exceeds 40mg h-1cm-2, and the Faraday efficiency can be maintained above 90% within different nitrate concentration ranges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710797A_ABST
    Figure CN119710797A_ABST
Patent Text Reader

Abstract

The invention provides a foamed nickel loaded phosphorus modified cobalt-copper bimetallic catalytic electrode, a preparation method thereof and application of the foamed nickel loaded phosphorus modified cobalt-copper bimetallic catalytic electrode in electro-catalysis nitrate reduction. According to the prepared foamed nickel loaded phosphorus modified cobalt-copper bimetallic catalytic electrode, the phosphorus modified cobalt-copper bimetallic catalyst (P-coated Cu-Co) is loaded on foamed nickel through an electrodeposition method and used for electrocatalysis of an electrochemical reaction for reducing nitrate to prepare ammonia, the P-coated Cu-Co catalyst can enable two-step cascade reaction (NO3 <-> to NO2 <-> and then to NH3) to be more harmonious, and the catalytic performance of the foamed nickel loaded phosphorus modified cobalt-copper bimetallic catalytic electrode is improved. According to the present invention, with the application of the catalyst, the accumulation of excessive NO2 <-> is avoided, the excellent ammonia synthesis performance is achieved by optimizing the two-step series reaction, and the Faraday efficiency exceeds 95% and the ammonia yield exceeds 40 mg h <-1 > cm <-2 > when the external voltage is-0.4 V vs RHE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode, a preparation method thereof, and application thereof in electrocatalytic nitrate reduction. Background Art

[0002] Ammonia (NH3) is a common compound that is considered not only as a versatile raw material for the synthesis of fertilizers, pharmaceuticals, dyes, etc., but also as a next-generation clean fuel because of its high energy density and zero carbon emissions. Currently, industrial-scale ammonia synthesis still relies on the energy-intensive Haber-Bosch process, which requires harsh conditions of 400-500°C and 150-300atm, consumes 2% of the world's energy and emits 1.4% of carbon dioxide each year. In recent years, electrochemical synthesis of ammonia at room temperature has become a promising sustainable alternative.

[0003] Nitrogen reduction reaction is an ideal electrochemical ammonia synthesis reaction that uses atmospheric N2 and water to synthesize ammonia under aqueous solution conditions. However, the solubility of N2 is low (0.02 g L -1 ), high bond energy of N≡N triple bond (941 kJ mol -1 ) and the violent hydrogen evolution reaction resulted in ammonia yield and Faradaic efficiency far below the target of the US Department of Energy REFUEL program (yield > 60 mg h -1 cm -2 , Faraday efficiency > 90%). In addition, nitric acid-rich wastewater is considered as another nitrogen source for electrochemical ammonia synthesis. Due to the higher solubility of nitrate (880 g L -1 ), N=O has lower bond energy (204kJ mol -1 ), while achieving simultaneous removal of nitrates from wastewater, the production of ammonia by nitric acid electroreduction reaction (NO3RR) is a promising path for industrial production, which is attractive from both energy and environmental perspectives.

[0004] NO3RR involves a multi-step proton-coupled electron transfer process and inadequate utilization of intermediates, which poses a challenge to the selectivity of ammonia synthesis. Among the many byproducts, the *NO2 intermediate that is easily desorbed in large quantities leads to a large amount of NO in the electrolyte. 2- Carryover is the most common and unexpected problem, reducing the selectivity of ammonia. Inspired by the microbial denitrification process, NO 3- The conversion to NH3 is considered as a two-step cascade reaction: in the first step, one active site mainly completes NO 3- to NO 2- conversion (initial 2e-process); in the second step, another active site accelerates NO 2-To NH3 conversion (subsequent 6e-process). Studies have shown that Cu phase is often used to achieve the first step of NO 3- to NO 2- The Co phase is in NO 2- However, the two mismatched active phases may still lead to low ammonia yield or large amounts of NO 2- Cumulatively, it is very important to achieve proper nitrite generation in the first active phase while maintaining excellent nitrite conversion capacity in the second active phase. Summary of the invention

[0005] In view of the defects of the prior art, the object of the present invention is to provide a nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode and a preparation method thereof and application in electrocatalytic nitrate reduction.

[0006] To achieve the above purpose, the solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a nickel foam-supported phosphorus-modified cobalt-copper bimetallic catalytic electrode, comprising the following steps:

[0008] Step (1), preparation of nickel foam carrier: firstly subjecting the nickel foam sheet to ultrasonic treatment, then immersing it in a mixed solution of 2-methylimidazole and Zn(NO3)2·6H2O to react, forming a self-assembled MOFs material ZIF-8 on the surface of the nickel foam, then washing with deionized water and ethanol, and drying to obtain the nickel foam carrier;

[0009] Step (2), preparation of phosphorus-modified cobalt-copper bimetallic catalytic electrode: adopting electrodeposition method, using three-electrode system, the nickel foam carrier obtained in step (1) is used as working electrode, carbon rod is used as counter electrode, Ag / AgCl is used as reference electrode, the electrodeposition solution is prepared by the following components: CoSO4·7H2O, CuSO4·5H2O, C6H5Na3O7, Na2HPO3 and (NH4)2SO4 are dissolved in deionized water, and electrodeposition is carried out at a potential of -1V vs.RHE to obtain a catalytic electrode in which phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) is loaded on the nickel foam carrier.

[0010] Preferably, in step (1), the sheet-like nickel foam is ultrasonically treated in 1-5 mol / L hydrochloric acid, anhydrous ethanol and deionized water in sequence, the ultrasonic frequency of the ultrasonic treatment is 60-100 Hz, and the ultrasonic treatment is carried out in the hydrochloric acid, anhydrous ethanol and deionized water for 8-15 minutes respectively; then, it is immersed in a mixed solution of 2-methylimidazole and Zn(NO3)2·6H2O, and reacted at room temperature for 10-14 hours, wherein the molar ratio of 2-methylimidazole to Zn(NO3)2·6H2O is (1-10):1.

[0011] Preferably, step (2) further comprises the following step: heating the nickel foam carrier obtained in step (1) to 450-550° C. and maintaining the temperature in an argon atmosphere for 1-3 hours.

[0012] Preferably, step (2) further comprises the following steps: washing the electrodeposited product with deionized water and ethanol, and drying.

[0013] Preferably, in step (2), CoSO4·7H2O:CuSO4·5H2O:C6H5Na3O7:Na2HPO3:(NH4)2SO4=(1-5):1:(1-5):(8-15):(1-5), preferably (1-3):1:(3-5):(10-12):(1-3), more preferably 2:1:4:11:2.

[0014] In a second aspect, the present invention also provides a nickel foam loaded phosphorus-modified cobalt-copper bimetallic catalytic electrode prepared by the preparation method as described above, which is a catalytic electrode in which a phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) is loaded on a nickel foam carrier.

[0015] Preferably, the phosphorus modified cobalt-copper bimetallic catalyst (P@Cu-Co) has a Cu loading ratio of 0.02-0.2wt%, preferably 0.02-0.1wt%, more preferably 0.08-0.1wt%, and a Co loading ratio of 0.01-0.1wt%, preferably 0.01-0.05wt%, more preferably 0.04-0.05wt%; the atomic ratio of P, Cu and Co is (8-15):1:(1-5), preferably (10-12):1:(1-3), more preferably 11:1:2; the power density of the phosphorus modified cobalt-copper bimetallic catalyst (P@Cu-Co) is 12-15mW cm -2 , at 52mA cm -2 conditions.

[0016] In a third aspect, the present invention also provides a use of the above-mentioned nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode in electrocatalytic nitrate reduction.

[0017] Preferably, the nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode is used as the working electrode, the graphite rod is used as the counter electrode, and the Hg / HgO electrode is used as the reference electrode to form a three-electrode system; the three-electrode system is placed in a nitrate-containing double-chamber H-type electrolytic cell, the cathode electrolyte is an Ar-saturated 1M KOH+0.1M NaNO3 solution (50mL), the anode electrolyte is 1M KOH (50mL), and the cathode chamber and the anode chamber are pretreated The membrane is separated and the electrocatalytic nitrate is converted into high-value-added ammonia using an Autolab electrochemical workstation.

[0018] Preferably, the Faradaic efficiency exceeds 95% and the ammonia yield exceeds 40 mgh at an applied voltage of -0.4 V vs RHE -1 cm -2 When the nitrate concentration changes from 0.05 to 0.25 mol / L, the Faraday efficiency can be maintained above 90%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The prepared nickel foam loaded phosphorus-modified cobalt-copper bimetallic catalytic electrode is loaded on the nickel foam by an electrodeposition method to electrocatalyze the electrochemical reaction of nitrate reduction to produce ammonia. The P@Cu-Co catalyst can make the two-step series reaction (NO3 - To NO2 - , and then to NH3) to be more coordinated and avoid excessive NO2 - Accumulatively, excellent ammonia synthesis performance was achieved by optimizing the two-step tandem reaction, with a Faradaic efficiency of over 95% and an ammonia yield of over 40 mg h at an applied voltage of -0.4 V vs RHE. -1 cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope (SEM) image of the phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) involved in the present invention.

[0022] Figure 2 Ammonia yield and Faraday efficiency diagram at different NaNO3 concentrations when the catalytic electrodes prepared in Examples 1 and 2 of the present invention were subjected to NO3RR.

[0023] Figure 3 When the catalytic electrodes prepared in Examples 1 and 2 of the present invention were subjected to NO3RR, the NH3 and NO2 - Partial current density ratio diagram.

[0024] Figure 4 Faraday efficiency chart at different voltages when the catalytic electrodes prepared in Examples 1 and 2 of the present invention perform NO3RR. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0026] The invention provides a nickel foam supported phosphorus-modified cobalt-copper bimetallic catalytic electrode. A phosphorus-modified Co-Cu bimetallic catalyst coating is deposited on a three-dimensional nickel foam carrier by an electrodeposition method. The electrodeposition method is beneficial to improving the intermolecular interaction force between active components Co and Cu and the three-dimensional nickel foam carrier. This bonding force can greatly improve the service life and stability of the catalyst.

[0027] The nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode provided by the present invention comprises the following steps:

[0028] Step (1), preparation of nickel foam carrier:

[0029] (1.1) First, subject the nickel foam sheet to ultrasonic treatment to remove stains on the surface of the nickel foam sheet.

[0030] In this step, in order to improve the removal efficiency, ultrasonic treatment can be performed in 3M hydrochloric acid, anhydrous ethanol and deionized water successively for, for example, 8-15 minutes, and the ultrasonic frequency can be 60-100 Hz, for example, 80 Hz.

[0031] In this step, the size of the sheet-like nickel foam may be (1-10) cm×(1-10) cm, for example, 2 cm×3 cm.

[0032] (1.2) The ultrasonically treated nickel foam is then immersed in a mixed solution of 2-methylimidazole and Zn(NO3)2·6H2O to react for 10-14 h at room temperature, and then washed with deionized water and ethanol and dried.

[0033] In this step, a self-assembled MOFs porous material ZIF-8 is formed on the surface of nickel foam by immersing it in a mixed solution of 2-methylimidazole and Zn(NO3)2·6H2O and reacting it at room temperature for 10-14 hours. The self-assembled MOFs porous material ZIF-8 can enhance the adsorption of Co and Cu metals in the subsequent electrodeposition process.

[0034] In this step, in the mixed solution, the molar ratio of 2-methylimidazole to Zn(NO3)2·6H2O is (1-10):1.

[0035] Subsequently, the nickel foam sample with self-assembled MOFs porous material ZIF-8 formed on the surface was washed with deionized water and ethanol, and then placed in a vacuum oven at 60-100° C. for 5-7 hours to dry the moisture on the surface of the nickel foam sample to obtain the desired nickel foam carrier.

[0036] Step (2), preparation of phosphorus-modified cobalt-copper bimetallic catalytic electrode:

[0037] According to the scheme of the present invention, the present invention uses transition metal Co and metal Cu as a composite material of the electrocatalytic electrode. It is confirmed by the embodiments of the present invention that the use of a bimetallic Co-Cu alloy material as the electrocatalytic electrode can effectively solve the problem that a single Co-based electrode requires a relatively negative working potential (-0.5 to -0.95 V vs. RHE) in the electrocatalytic nitrate reduction reaction (NO3RR) to achieve 1-5 mg h -1 cm -2 The problem of achieving a considerable ammonia yield and a high Faraday efficiency is solved. At the same time, compared with a single Co-based electrode or a single Cu-based electrode, the Co-Cu alloy material can exhibit higher electrocatalytic activity and better selectivity for a single product. The mechanism may be that since the metal Cu catalyst is the connection point of H*, it has excellent hydrogen adsorption and desorption capabilities, optimizes the reaction kinetics of NO3RR, and can improve the hydrogenation step at a more positive potential (≥-0.4V vs.RHE), greatly reducing the overpotential of NO3RR. On the other hand, it is necessary to better inhibit the hydrogen evolution reaction, because high hydrogen coverage tends to kinetically favor hydrogen evolution rather than NO3RR ammonia production, and transition metals (such as Fe, Co, Ni, Cu and Zn) can inhibit water dissociation and adjust the coverage of adsorbed hydrogen (*H), thereby inhibiting undesirable hydrogen evolution reactions. Therefore, the present invention accurately controls the appropriate amount of adsorbed hydrogen through a combination of transition metal Co and metal Cu to meet the specific hydrogenation requirements of NO3RR, improve the catalytic activity, and then achieve a high ammonia Faraday efficiency. At the same time, compared with platinum group metals (Ru, Rh, Pd) as metal catalysts composited with transition metal Co, metal Cu catalysts have lower costs and are more conducive to industrial production.

[0038] According to the solution of the present invention, the present invention adopts phosphorus-modified Co-Cu bimetallic (P@Cu-Co) as a composite material of the electrocatalytic electrode, and introduces phosphorus atoms into the metal lattices of Co and Cu. From the electronic structure point of view, the outermost electrons of the phosphorus atom are 5, and its properties are active. In addition, the electronegativity difference between phosphorus and metal is large. Such filling can reduce the strength between metal bonds, which is beneficial to the adsorption and desorption of hydrogen during the hydrolysis process of NO3RR reaction.

[0039] However, if the electronegativity difference between metal and phosphorus is too large, it will be unfavorable for the delocalization of electrons in the catalyst. Cobalt and phosphorus have a moderate electronegativity difference. The introduction of phosphorus can make the metal sites with strong hydrogen adsorption ability easier to desorb hydrogen, thereby protecting the metal sites with strong hydrogen adsorption ability from deactivation. The introduction of phosphorus reduces the adsorption energy of hydrogen atoms and exhibits excellent hydrogen evolution catalytic activity.

[0040] Meanwhile, the conductivity of the phosphorus modified product of single metal Co is relatively low, while the phosphorus modified complex of bimetallic Co-Cu used in the present invention can exhibit stronger electron migration ability, effectively enhancing the conductivity and catalytic activity of the catalyst composite material.

[0041] The higher the phosphorus content in the catalyst, the higher the hydrogen evolution activity of the catalyst. However, excessive phosphorus modification can easily lead to a reduction in free electrons in the catalyst, which affects the conductivity of the material and ultimately affects the hydrogen evolution activity. Therefore, it is necessary to regulate the phosphorus modification method and concentration. In the present invention, in the phosphorus-modified Co-Cu bimetallic (P@Cu-Co) composite material used in the present invention, the atomic ratio of P, Cu and Co is (8-15):1:(1-5), which is proven to ensure the best hydrogen evolution activity of the catalyst, preferably (10-12):1:(1-3), and more preferably 11:1:2.

[0042] The present invention adopts an electrodeposition method to electrodeposit a phosphorus-modified cobalt-copper bimetallic catalyst on the surface of the nickel foam obtained in step (1), which specifically comprises the following steps:

[0043] (2.1) Prepare the electrolyte solution for electrodeposition:

[0044] CoSO4·7H2O, CuSO4·5H2O, C6H5Na3O7, Na2HPO3 and (NH4)2SO4 are dissolved in deionized water, wherein the molar ratio of CoSO4·7H2O, CuSO4·5H2O, C6H5Na3O7, Na2HPO3 and (NH4)2SO4 is (1-5):1:(1-5):(8-15):(1-5), preferably (1-3):1:(3-5):(10-12):(1-3), and more preferably 2:1:4:11:2.

[0045] (2.2) Electrodeposition using a three-electrode system:

[0046] The nickel foam carrier obtained in step (1) is used as a working electrode, the carbon rod is used as a counter electrode, and Ag / AgCl is used as a reference electrode. The above electrolyte solution is an electrodeposition solution, and electrodeposition is performed at a potential of -1 V vs. RHE. The nickel foam carrier deposited with the phosphorus-modified Co-Cu bimetallic catalyst coating is then washed with deionized water and anhydrous ethanol, and then placed in a vacuum oven at 60-100° C. and dried overnight to obtain a final phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) loaded on the nickel foam carrier. Catalytic electrode.

[0047] In this step, in order to improve the quality and speed of electrodeposition, the nickel foam carrier obtained in step (1) can be heated to 450-550°C (the heating rate can be 5-10°C / min) and maintained in an argon atmosphere for 1-3 hours. In this way, the electrodeposition can be completed at a potential of -1V vs. RHE in 10-30 minutes.

[0048] According to the preparation method of the present invention, the present invention first forms a self-assembled MOFs porous material ZIF-8 on the surface of the nickel foam three-dimensional carrier, so that in the subsequent electrodeposition process, the P@Cu-Co composite material is coated on the surface of the self-assembled MOFs porous material ZIF-8. Figure 1 The scanning electron microscope (SEM) image of the phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) prepared by the present invention is given. Figure 1 It can be seen that phosphorus-modified Cu nanosphere particles and phosphorus-modified Co nanosheets are formed on the surface of the three-dimensional nickel foam support with the self-assembled MOFs porous material ZIF-8. The P@Cu-Co composite material with the above structure grown on the self-assembled MOFs porous material ZIF-8 on the three-dimensional nickel foam support has been proven to provide the largest specific surface area and the smallest electron transport resistance. At the same time, more voids are easily generated under the action of current, which is conducive to the precipitation of product gas and prevents the active sites from being covered by gas, which can effectively increase the number of active sites of the catalyst.

[0049] The nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode prepared by the preparation method of the present invention is a catalytic electrode in which a phosphorus modified cobalt-copper bimetallic catalyst (P@Cu-Co) is loaded on a nickel foam carrier, wherein the loading ratio of Cu is 0.02-0.2wt%, preferably 0.02-0.1wt%, more preferably 0.08-0.1wt%, and the loading ratio of Co is 0.01-0.1wt%, preferably 0.01-0.05wt%, more preferably 0.04-0.05wt%; the atomic ratio of P, Cu and Co is (8-15):1:(1-5), preferably (10-12):1:(1-3), more preferably 11:1:2; and the power density of the phosphorus modified cobalt-copper bimetallic catalyst (P@Cu-Co) is 12-15mW cm -2 , at 52mA cm -2 conditions.

[0050] The present invention also provides an application of a nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode prepared by the method as described above in electrocatalytic nitrate reduction.

[0051] The nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode prepared by the method of the present invention is proved to be suitable for the application of the reactor flowing through the electrocatalytic nitrate reduction. The P@Cu-Co composite catalyst composed of P-Cu nanospheres and P-Co nanosheets can make the two-step series reaction of the electrocatalytic nitrate reduction reaction (from NO3 - To NO2 - , and then to NH3) to be more coordinated and avoid excessive NO2 - The results showed that P-Cu inhibited the desorption of NO2 and made NO2 - It is more suitable to release in the electrolyte, and P-Co has better absorption and conversion desorption of NO2 - ability, thanks to its thermodynamic advantages and the contribution of active hydrogen.

[0052] At the same time, the present invention also provides an electrochemical system for electrocatalytic nitrate reduction, in which the foam nickel-loaded phosphorus-modified cobalt-copper bimetallic catalytic electrode is used as a working electrode, a graphite rod is used as a counter electrode, and a Hg / HgO electrode is used as a reference electrode to form a three-electrode system; the three-electrode system is placed in a double-chamber H-type electrolytic cell containing nitrate, the cathode electrolyte is an Ar-saturated 1M KOH+0.1MNaNO3 solution (50mL), the anode electrolyte is 1M KOH (50mL), and the cathode chamber and the anode chamber are pretreated with The membrane is separated and the electrocatalytic nitrate is converted into high-value-added ammonia using an Autolab electrochemical workstation.

[0053] The examples of the present invention confirm that the electrochemical system for electrocatalytic nitrate reduction using the nickel foam-supported phosphorus-modified cobalt-copper bimetallic catalytic electrode of the present invention can achieve a Faradaic efficiency of more than 95% and an ammonia yield of more than 40 mg h-1 at an applied voltage of -0.4 V vs RHE. -1 cm -2 When the nitrate concentration changes from 0.05 to 0.25 mol / L, the Faraday efficiency can be maintained above 90%.

[0054] The present invention is further described below in conjunction with examples, the purpose of which is to better understand the content of the present invention and reflect the essential characteristics of the present invention, so the examples cited should not be regarded as limiting the scope of protection of the present invention. It is also particularly pointed out here that the specific experimental methods and equipment involved in the examples are conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified, and the reagents involved are commercially available unless otherwise specified.

[0055] Embodiment 1:

[0056] A method for preparing a nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode comprises the following steps:

[0057] Step S1: treating commercial nickel foam with 3M hydrochloric acid, anhydrous ethanol and deionized water at an ultrasonic frequency of 80 Hz for 10 minutes respectively;

[0058] Step S2: 2-methylimidazole solution (0.8M) and Zn(NO3)2·6H2O solution (0.1M) were mixed in a volume ratio of 1:1; the ultrasonically treated nickel foam was immersed in the mixed solution and reacted at room temperature for 12 hours to form a self-assembled MOFs material ZIF-8 on the surface of the nickel foam; the sample was washed with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 6 hours to obtain a nickel foam carrier;

[0059] Step S3: adopting the electrodeposition method, using a three-electrode system, heating the nickel foam carrier obtained in step (1) to 500°C (heating rate of 5°C / min), keeping it in an argon atmosphere for 2 hours as a working electrode, a carbon rod as a counter electrode, and Ag / AgCl as a reference electrode; the electrodeposition solution is prepared from the following components: CoSO4·7H2O (0.1M), CuSO4·5H2O (0.05M), C6H5Na3O7 (0.2M), Na2HPO3 (0.55M) and (NH4)2SO4 (0.2M), dissolved in deionized water; electrodeposition is carried out for 10 minutes at a potential of -1V vs.RHE, and after obtaining the precipitate, it is washed with deionized water and ethanol, and then dried in a vacuum oven at 60°C overnight to obtain the final nickel foam supported phosphorus modified cobalt-copper bimetallic catalytic electrode.

[0060] Electrochemical tests were performed in an H-type electrolytic cell with a three-electrode configuration using an Autolab electrochemical workstation. The anode and cathode compartments of the H-type electrolytic cell were pre-treated with The experiment was carried out at room temperature and pressure, using a three-electrode system, in which the working electrode was a 1cm×1cm nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode sample, the reference electrode was a Hg / HgO electrode, and the counter electrode was a graphite rod. All potential values ​​were converted to the reversible hydrogen electrode scale. The cathode electrolyte was Ar-saturated 1MKOH+0.01-0.5M NaNO3 solution (50mL), and the anode electrolyte was 1M KOH (50mL). Constant potential tests were carried out at different potentials for 30 minutes. After the test, the cathode electrolyte was collected and the products of nitrate reduction were analyzed using a UV-vis spectrometer.

[0061] The SEM image of the prepared phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) is shown in Figure 1 shown.

[0062] The prepared phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) has a power density of 12-15 mW cm -2 , at 52mAcm -2 conditions.

[0063] Embodiment 2:

[0064] The preparation of electrode materials and the method for catalytic reduction of nitrates are as in Example 1, except that Na2HPO3 is not added in step S3, thereby obtaining a nickel foam-supported cobalt-copper bimetallic (Cu-Co) catalytic electrode.

[0065] The power density of the prepared cobalt-copper bimetallic catalyst (Cu-Co) is 10-12 mW cm -2 , at 40mAcm -2 conditions.

[0066] When the catalytic electrodes obtained in Example 1 and Example 2 were subjected to NO3RR, the ammonia yield and the Faraday efficiency were as follows at different NaNO3 solution concentrations: Figure 2 shown.

[0067] When the catalytic electrodes obtained in Example 1 and Example 2 were subjected to NO3RR, NH3 and NO2 - The partial current density is such as Figure 3 shown.

[0068] When the catalytic electrodes obtained in Example 1 and Example 2 were subjected to NO3RR, the Faraday efficiency was as follows at different voltages: Figure 4 shown.

[0069] from Figure 2 , Figure 3 and Figure 4 It can be seen that compared with the nickel foam loaded cobalt-copper bimetallic (Cu-Co) catalytic electrode without phosphorus modification in Example 2, the ammonia yield and Faradaic efficiency of the nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode obtained in Example 1 are greatly improved. When the applied voltage is -0.4 V vs RHE, the Faradaic efficiency exceeds 95%, and the ammonia yield exceeds 40 mg h -1 cm -2 When the nitrate concentration changes from 0.05 to 0.25 mol / L, the Faraday efficiency can be maintained above 90%.

[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode, characterized in that: The steps include: Step (1), preparation of nickel foam carrier: firstly subjecting the nickel foam sheet to ultrasonic treatment, then immersing it in a mixed solution of 2-methylimidazole and Zn(NO3)2·6H2O to react, forming a self-assembled MOFs material ZIF-8 on the surface of the nickel foam, then washing with deionized water and ethanol, and drying to obtain the nickel foam carrier; Step (2), preparation of phosphorus-modified cobalt-copper bimetallic catalytic electrode: adopting electrodeposition method, using three-electrode system, the nickel foam carrier obtained in step (1) is used as working electrode, carbon rod is used as counter electrode, Ag / AgCl is used as reference electrode, the electrodeposition solution is prepared by the following components: CoSO4·7H2O, CuSO4·5H2O, C6H5Na3O7, Na2HPO3 and (NH4)2SO4 are dissolved in deionized water, and electrodeposition is carried out at a potential of -1V vs.RHE to obtain a catalytic electrode in which phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) is loaded on the nickel foam carrier.

2. The preparation method according to claim 1, characterized in that: In step (1), the sheet-like nickel foam is ultrasonically treated in 1-5 mol / L hydrochloric acid, anhydrous ethanol and deionized water in sequence, the ultrasonic frequency of the ultrasonic treatment is 60-100 Hz, and the ultrasonic treatment is carried out in the hydrochloric acid, anhydrous ethanol and deionized water for 8-15 minutes respectively; then, it is immersed in a mixed solution of 2-methylimidazole and Zn(NO3)2·6H2O, and reacted at room temperature for 10-14 hours, wherein the molar ratio of 2-methylimidazole to Zn(NO3)2·6H2O is (1-10):

1.

3. The preparation method according to claim 1, characterized in that: Step (2) also includes the following steps: heating the nickel foam carrier obtained in step (1) to 450-550° C. and maintaining the temperature in an argon atmosphere for 1-3 hours.

4. The preparation method according to claim 1, characterized in that: Step (2) also includes the following steps: washing the electrodeposited product with deionized water and ethanol, and drying.

5. The preparation method according to claim 1, characterized in that: In step (2), CoSO4·7H2O:CuSO4·5H2O:C6H5Na3O7:Na2HPO3:(NH4)2SO4=(1-5):1:(1-5):(8-15):(1-5), preferably (1-3):1:(3-5):(10-12):(1-3), more preferably 2:1:4:11:

2.

6. A nickel foam loaded phosphorus modified cobalt-copper bimetallic catalytic electrode prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The catalytic electrode is a phosphorus-modified cobalt-copper bimetallic catalyst (P@Cu-Co) loaded on a nickel foam carrier.

7. The nickel foam supported phosphorus modified cobalt-copper bimetallic catalytic electrode according to claim 6, characterized in that: The phosphorus modified cobalt-copper bimetallic catalyst (P@Cu-Co) has a Cu loading ratio of 0.02-0.2wt%, preferably 0.02-0.1wt%, more preferably 0.08-0.1wt%, and a Co loading ratio of 0.01-0.1wt%, preferably 0.01-0.05wt%, more preferably 0.04-0.05wt%; the atomic ratio of P, Cu and Co is (8-15):1:(1-5), preferably (10-12):1:(1-3), more preferably 11:1:2; the power density of the phosphorus modified cobalt-copper bimetallic catalyst (P@Cu-Co) is 12-15mW cm -2 , at 52mA cm -2 conditions.

8. Use of the nickel foam supported phosphorus modified cobalt-copper bimetallic catalytic electrode as claimed in claim 6 or 7 in electrocatalytic nitrate reduction.

9. The use according to claim 8, characterized in that: The foam nickel-loaded phosphorus-modified cobalt-copper bimetallic catalytic electrode is used as the working electrode, the graphite rod is used as the counter electrode, and the Hg / HgO electrode is used as the reference electrode to form a three-electrode system; the three-electrode system is placed in a double-chamber H-type electrolytic cell containing nitrate, the cathode electrolyte is an Ar-saturated 1M KOH+0.1MNaNO3 solution (50mL), the anode electrolyte is 1M KOH (50mL), and the cathode chamber and the anode chamber are pretreated with 117 membrane separation, using the Autolab electrochemical workstation, the electrocatalytic nitrate conversion into high value-added ammonia reaction.

10. The use according to claim 9, characterized in that: At an applied voltage of -0.4 V vs RHE, the Faradaic efficiency exceeded 95% and the ammonia yield exceeded 40 mg h -1 cm -2 When the nitrate concentration changes from 0.05 to 0.25 mol / L, the Faraday efficiency can be maintained above 90%.